The Effect of Financial Ratios on Company Value in Food And Beverage Companies on The IDX - Sulfati, Andi; Jamali, Hisnol (Nusantara Economics and Entrepreneurships Journals, 2025)
Companies looking for investors aim to add capital, so the more capital the company has, the more food and beverages the company produces so that it can increase the company's profitability, if profitability increases, the company's value will also increase as well as investment decisions, if the more investment, the higher the company's value. The purpose of this study is to analyze the effect of Financial Ratios on Company Value in Food and Beverage Companies Listed on the IDX in 2020-2023. The method used is a quantitative research method. The conclusion of this study is that there is a partial influence of the DER, TAG and ROE variables onEPS In Food and Beverage Sector Companies On The Indonesia Stock Exchange2020-2023 and the existence ofthe influence of DER, TAG and ROE variablessecara together or simultaneously on EPS in the Food and Beverage Sector Companies on the Indonesia Stock Exchange2020-2023